Hubungan Pengetahuan dengan Tingkat Kecemasan Bidan dalam Memberikan Pertolongan Persalinan di Era Pandemi Covid-19 - Siti Khotimah (Poltekkes Kemenkes Medan, 2020)
Introduction: Labor is an important event in a woman's life. One of the main tasks of a midwife is to assist in the delivery process. In the Covid-19 pandemic era, all people were required to carry out activities according to the health protocol, especially midwives who acted as implementers, in this case midwives' knowledge was prioritized so as not to influence the mindset that had an impact on anxiety. This study aimed to determine the relationship of knowledge with the level of anxiety of midwives in assisting childbirth in the covid-19 pandemic era. Methods: This research is a descriptive study which is included in the type of Analytical Survey using a Cross Sectional approach. The technique used in sampling is a non probability sampling technique with a purposive sampling method. The sample used in this study was midwives who worked as implementing midwives with a total of 35 respondents in the Dharmasraya Regency. Results and Discussion: There was a significant relationship between knowledge and the level of anxiety of respondents in providing childbirth assistance to patients in the co-19 pandemic era. Conclusion: Good midwife knowledge about the Covid-19 pandemic, especially in providing health services to the community, especially in assisting childbirth assistance in patients in the Covid-19 pandemic era can affect good psychiatric health for midwives and not experience a bad anxiety level.